Texture and trace element characteristics of quartz in the Dongyuan porphyry W deposit, eastern China - Liu Yang; Yuanyuan Tian; Quanzhong Li; Jun Yan; Jiancheng Xie (Solid Earth Sciences, 2023)
Most W mineralization in the world is genetically related with highly fractionated granites, but little is known about ore-forming fluid evolution of W mineralization associated with weakly fractionated granites. To reveal the ore-forming fluid evolution of W mineralization related to the weakly fractionated granites, a combined study of field and petrographic observations, mineralogical, morphological, and in-situ geochemical data of different-type quartz from Dongyuan porphyry W deposit in the world-class Jiangnan W belt, China, was carried out. The petrographic observation and cathodoluminescence (CL) imaging revealed the quartz in the Dongyuan W deposit can be divided into hydrothermal quartz (Qz1 with core-edge structure, and Qz2 with oscillating zone) in the mineralized alteration zone, and magmatic quartz (Qz3 with inherited core) in granodiorite porphyry. The LA-ICP-MS results of the Dongyuan quartz samples show that Al may enter the quartz structure with trivalent Al3+ instead of Si4+, monovalent alkali metals and bivalent (Ge2+, Sr2+) cations is mainly of charge compensators in quartz, while Ti possibly is in the form of microinclusions of titanium-containing minerals in quartz. The integrated interpretation of the trace element compositions (e.g., Al and Ti contents, Al/Na ratios) and CL texture of quartz indicate high temperature (>400 °C) and uniform Al-rich acidic fluid are conducive to W precipitation of the Dongyuan deposit. Furthermore, trace element compositions (e.g., Ge, Al) and micro-textures of quartz have the potential for distinguishing magmatic and hydrothermal quartz in the Dongyuan W deposit.